2015
DOI: 10.14348/molcells.2015.0051
|View full text |Cite
|
Sign up to set email alerts
|

miR-335 Targets SIAH2 and Confers Sensitivity to Anti-Cancer Drugs by Increasing the Expression of HDAC3

Abstract: We previously reported the role of histone deacetylase 3 (HDAC3) in response to anti-cancer drugs. The decreased expression of HDAC3 in anti-cancer drug-resistant cancer cell line is responsible for the resistance to anti-cancer drugs. In this study, we investigated molecular mechanisms associated with regulation of HDAC3 expression. MG132, an inhibitor of proteasomal degradation, induced the expression of HDAC3 in various anti-cancer drug-resistant cancer cell lines. Ubiquitination of HDAC3 was observed in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…Moreover, the GO functional annotation analysis was performed and found that the four genes were annotated with drug responses related GO terms (Table S6), such as cell cycle, apoptotic process, and DNA damage response. In the STAD DRCEs, four lncRNA, RP11‐473O4.3, LINC01184, LINC00641, and ENSG00000248175, competed for binding to miR‐331, miR‐335, and miR‐106b, which are known to be associated with chemotherapy resistance (Feng et al ., 2011; Kim et al ., 2015; Xia et al ., 2008), thereby regulating their target genes. Consequently, the six DRCEs, hsa‐miR‐335_KLF8_LINC00641, hsa‐miR‐106b_APC_ENSG00000248175, hsa‐miR‐106b_APC_LINC01184, hsa‐miR‐106b_CCND2_ENSG00000248175, hsa‐miR‐331_ATRX_ENSG00000248175, and hsa‐miR‐331_ATRX_RP11‐473O4.3, may affect 5‐FU drug responses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the GO functional annotation analysis was performed and found that the four genes were annotated with drug responses related GO terms (Table S6), such as cell cycle, apoptotic process, and DNA damage response. In the STAD DRCEs, four lncRNA, RP11‐473O4.3, LINC01184, LINC00641, and ENSG00000248175, competed for binding to miR‐331, miR‐335, and miR‐106b, which are known to be associated with chemotherapy resistance (Feng et al ., 2011; Kim et al ., 2015; Xia et al ., 2008), thereby regulating their target genes. Consequently, the six DRCEs, hsa‐miR‐335_KLF8_LINC00641, hsa‐miR‐106b_APC_ENSG00000248175, hsa‐miR‐106b_APC_LINC01184, hsa‐miR‐106b_CCND2_ENSG00000248175, hsa‐miR‐331_ATRX_ENSG00000248175, and hsa‐miR‐331_ATRX_RP11‐473O4.3, may affect 5‐FU drug responses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the major roles of miRNAs in regulating protein expression in general, it is reasonable to infer that targeting miRNAs could be a promising approach to overcome drug resistance. A growing body of data indicates that miR-335 plays an essential role in drug resistance (25)(26)(27). Kim et al found that miR-335/SIAH2/HDAC3 axis regulates the response to anticancer drugs (25).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of data indicates that miR-335 plays an essential role in drug resistance (25)(26)(27). Kim et al found that miR-335/SIAH2/HDAC3 axis regulates the response to anticancer drugs (25). Another study revealed that the expression of miR-335 was downregulated in all the ovarian cancer resistant cells, suggesting a direct involvement in the development of chemoresistance (26).…”
Section: Introductionmentioning
confidence: 99%
“…The expression level of HDAC3 has been shown to be down-regulated in various cancer cell lines that are resistant to anti-cancer drugs ( Kim et al, 2014 ). The expression of HDAC3 is controlled via ubiquitination ( Kim et al, 2015b ). miR-335 increases the expression of HDAC3 by preventing SIAH2 from inducing ubiquitination of HDAC3 ( Kim et al, 2015b ).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of HDAC3 is controlled via ubiquitination ( Kim et al, 2015b ). miR-335 increases the expression of HDAC3 by preventing SIAH2 from inducing ubiquitination of HDAC3 ( Kim et al, 2015b ). The selective inhibition of HDAC3 protects beta cells from cytokine-induced apoptosis ( El-Khoury et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%